2023
DOI: 10.3389/fimmu.2023.1067369
|View full text |Cite
|
Sign up to set email alerts
|

Human lymphocytes mobilized with exercise have an anti-tumor transcriptomic profile and exert enhanced graft-versus-leukemia effects in xenogeneic mice

Abstract: BackgroundEvery bout of exercise mobilizes and redistributes large numbers of effector lymphocytes with a cytotoxic and tissue migration phenotype. The frequent redistribution of these cells is purported to increase immune surveillance and play a mechanistic role in reducing cancer risk and slowing tumor progression in physically active cancer survivors. Our aim was to provide the first detailed single cell transcriptomic analysis of exercise-mobilized lymphocytes and test their effectiveness as a donor lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Recent work has shown that these mobilized cells subsequently infiltrate tumors and are essential in constraining tumor growth in several murine cancer models ( 42 ). We recently introduced the innovative concept that lymphocytes mobilized by exercise enhance the graft-versus-leukemia (GvL) effects of donor lymphocyte infusions ( 35 ). In addition, an exercise session can improve the ex vivo production and effectiveness of virus-specific T-cells, γδ T-cells, and tumor antigen-specific T-cells ( 43–45 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work has shown that these mobilized cells subsequently infiltrate tumors and are essential in constraining tumor growth in several murine cancer models ( 42 ). We recently introduced the innovative concept that lymphocytes mobilized by exercise enhance the graft-versus-leukemia (GvL) effects of donor lymphocyte infusions ( 35 ). In addition, an exercise session can improve the ex vivo production and effectiveness of virus-specific T-cells, γδ T-cells, and tumor antigen-specific T-cells ( 43–45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mycoplasma testing was routinely performed but we did not authenticate the cell line. K562-luc2 cells were maintained at 37°C, 5% CO 2 in Iscove's DMEM supplemented with 10% FBS and 8 µg/mL blasticidin and prepared for tail vein injection as described previously ( 35 ). Mice were irradiated with 100 cGy, using a Cesium 137 irradiator, one day (day −2) before intravenous injection of expanded Vγ9Vδ2+ T-cells on day −1, mice not receiving expanded γδ T-cells (tumor-only) were injected with an equal volume of saline on the same day.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 Additionally, 3 genes ( PMEL, TYRP1 , and EDNRB ) overexpressed in the exhausted subpopulations were associated with poor prognosis. 7 It is conceivable that the information provided by scRNA-seq could also help to characterize the molecular mechanisms underlying the effects of physical exercise on anticancer immune function as well as on the complex tumor microenvironment, as recently illustrated by 2 relevant studies 8 , 9 ( Fig. 1 ).…”
mentioning
confidence: 96%
“…1 Main findings from single-cell analysis. (A) Acute and regular exercise improve cancer immunosurveillance; (B) Findings from Savage et al 8 ; (C) Findings from Batatinha et al 9 This figure was created using BioRender (https://biorender.com/). APC = antigen presenting cells; IFN = interferon; MHC = major histocompatibility complex; OXPHOS = oxidative phosphorylation; PBMCs = peripheral blood mononuclear cells; scRNA-seq = single-cell RNA sequencing; TAM = tumor-associated macrophages.…”
mentioning
confidence: 99%